Oxidative C–C bond formation and C–N bond cleavage catalyzed by complexes of copper(i) with acridine based (E N E) pincers (E = S/Se), recyclable as a catalyst. Issue 27 (10th June 2019) - Gupta, Sonu; Dubey, Pooja; Singh, Ajai K.; Jain, Nidhi
Abstract : Structurally characterized 1 mol% Cu(i )-complexes efficiently catalyze the coupling of tertiary amines with terminal alkynes and C–N bond cleavage. Abstract : Copper(i ) complexes of 4, 5-bis((phenylthio/seleno)methyl)acridine, [CuL Br] (C1 andC2 ) (L =L1 /L2 ; pincer type (E N E) ligand), were synthesized and found to be thermally stable, and moisture and air insensitive. The complexes and ligands were characterized by multinuclei NMR and single crystal X-ray diffraction. In both complexesC1 andC2, ligandsL1 andL2 coordinate with Cu in a pincer mode furnishing two six-membered chelate rings, with the distorted tetrahedral geometry of donor atoms around Cu. The Cu–S and Cu–Se bond lengths (Å) are 2.2482(17)–2.2979(16) and 2.3603(14)–2.4177(13) respectively. These complexes served as efficient catalysts for cross dehydrogenative coupling of unactivated tertiary amines with unactivated terminal alkynes, and cleavage of the benzylic (C–N) bond of N, N dimethylbenzylamines under oxidative solvent-free conditions. The reactions were found to be highly selective, and no over-oxidation to acid was observed. A low catalytic loading of 1.0 mol% was good enough to bring about both these transformations with recyclability up to five times.